MOST COMMON PATHOGENIC ORGANISMS CAUSING URINARY TRACT INFECTION IN DIABETIC VERSUS NONDIABETIC PATIENTS AND THEIR ANTIBIOTIC SENSITIVITY PATTERNS - Shaukat , Sundas; Hussain, Ashfaq; Shaukat, Mazhar; Shaukat, Laila; Zamir, Nayab (Infectious Diseases Journal of Pakistan, 2023)
Background: To identify the most common pathogen causing urinary tract infection in diabetics versus nondiabetics and their antibiotic susceptibility. Material and Method: This case control study was conducted Combined Military Hospital Mardan, August 2022 - January 2023. Using a stratified sampling technique 90 patients were divided into Group DM and Group NDM with 45 participants in each group. History, demographic characteristics, symptomatology and empirical treatment prescribed was recorded for each patient and midstream urine sample was collected. Urine culture and sensitivity was performed to identify the organisms and antibiotic susceptibility of the causative agent. Recorded variables included the organisms identified and their sensitivity patterns. Results: Gender distribution revealed males were 17(37.8%) versus 12(26.7%) from Group DM and Group NDM with a mean age of the participants was 54.64 ± 9.74 years. Clinical features like history of UTI, history of catheterization, asymptomatic bacteriuria was seen more in diabetics as compared to non-diabetics with a p value of < 0.05. Escherichia Coli was the most common causative organism found in 44 (48.5%) out of 90 patients in both diabetic and non-diabetic patients. Antibiotic susceptibility revealed increased sensitivity of Escherichia Coli to Fosfomycin (88.6%) followed by nitrofurantoin (81.8%) and meropenem (75%). Conclusion: Escherichia coli is the most common isolate causing urinary tract infection in diabetic and non-diabetic patients which shows greatest sensitivity to Fosfomycin, nitrofurantoin and meropenem. Key Words: Antibiotic susceptibility, Culture, Pathogen, Sensitivity.